AN ANALYSIS OF STUDENT STRATEGY IN COMPLETING TOEFL READING COMPREHENSION TEST - Dede Rohadi Fajri (Journal of English Language Teaching and Literature (JELTL), 2019)
This research aimed to find out the strategies used by students in completing TOEFL reading comprehension test, types of reading comprehension in TOEFL test that was difficult to be answered by students, the greatest challenges factor for students in completing reading comprehension in TOEFL test, and the score of the 2nd semester students of STTIKOM Insan Unggul Cilegon-Banten. This is a descriptive qualitative study based on observation, interview, questionnaire and test as the instruments of collecting data.The sample is 20 advanced STTIKOM undergraduate students at Cilegon-Banten in Academic year 2018/2019 who were asked to do a PBT TOEFL reading comprehension test.The result showed that inference (33%), vocabulary (40%) and unstated details (50%) questions are the most difficult types to be answered by students. Related to the strategy, three of the strategies (skimming and scanning, top down and guess meaning ) are used by students in answering reading comprehension in TOEFL test. The greatest challenges for students in answering TOEFL reading comprehension in TOEFL test are less motivation in reading a text, less practice and they did not mastering vocabulary well. In addition, the TOEFL score of STTIKOM Insan Unggul Cilegon-Banten was insufficient to achieve standardize test or low.